“Eu não fiz nada! O que eu estou fazendo aqui?” : narrativas de agressores em processos de violência doméstica e familiar contra a mulher - Rojas, Eliane Aparecida Montanha (2023)
The study of violence against women over the years has been gaining prominence in academic circles. The primary objective of this research is to analyze the narratives of women’s aggressors, based on two selected cases from the Specialized Court for Domestic and Family Violence Against Women in Cuiabá. From these documents, a study was conducted to understand the reasons behind certain responses and the common emotional and moral representations among various perpetrators of violence against women. Additionally, quantitative data available on the website of Civil Police of Mato Grosso was used for a better understanding of the subject and as parameters for reflecting on violent behaviors. Methodologically, a quantitative approach was employed to structure tables using simple averages and percentages. A qualitative methodology was also utilized, involving document research and description for the analysis of the cases. Currently, these cases are archived and in the public domain, ensuring the careful preservation of the identity and rights of the parties involved. It was observed that some emotional representations such as anger, contempt, fear, and disorientation, as well as moral representations like the belief that the victim is inferior, humiliation, and the imposition of power and control, are present in cases of domestic violence against women.